Child violence: from psechoanalysis to the reality of protecting children’s rights in Brasil. - Virna, Zhanna P.; Eyng, Ana Maria (Волинський національний університет імені Лесі Українки, 2024)
The purpose of the presented material is to summarize the basic psychoanalytic positions on the analysis of human aggressiveness and violent impulses, as well as to analyze the work of South American educators on the problem of violence within the recognition of human rights to a safe life. Methods. The defined theoretical and methodological direction of the analysis of child violence consists of research procedures, bibliographic review, psychoanalytic and socio-pedagogical research. Results. Psychoanalytic positions of interpretation of the phenomenon of violence are represented by Freud's classic generalizations about aggression, sadism and repression of libido. The conceptual understanding of the intrapsychic aspects of the child's violence is supplemented by the provisions of the theories of object relations through various forms of self-destruction of the individual. The socio-historical context of violence is revealed and it is emphasized that violence always contains the fact of violation by one person of the rights and freedoms of another person. The analysis of the works of Brazilian psychoanalysts reveals the specifics of experiencing the "feeling of colonization" in unconscious forms of repressed tension, confrontation and guilt. It is emphasized that various conflict traumas and states of social disintegration should begin with the awareness of just solidarity and human rights. It is also important to be aware of the rights of the child, which is in line with the doctrine of integral protection. The scientific achievements of the scientific school of Professor A.M. Eyng on the study of the problems of violence and children's rights are revealed. The basic positions of cooperation between Ukrainian and Brazilian scientists on the study of psychological norms of quality of life, mental health and well-being of children in humanitarian situations (poverty, wars, environmental disasters, forced displacement, etc.) are outlined.
Keywords: violence; aggression; self-destruction; sense of colonization; protection from poverty; children's rights; transference; mentalization; 316.624.3:159.99